Adeno-Associated Virus (AAV-DJ)—Cryo-EM Structure at 1.56 Å Resolution - Xie, Qing (Viruses, 2020)
Adeno-associated virus is the leading viral vector for gene therapy. AAV-DJ is a recombinant variant developed for tropism to the liver. The AAV-DJ structure has been determined to 1.56 Å resolution through cryo-electron microscopy (cryo-EM). Only apoferritin is reported in preprints at 1.6 Å or higher resolution, and AAV-DJ nearly matches the highest resolutions ever attained through X-ray diffraction of virus crystals. However, cryo-EM has the advantage that most of the hydrogens are clear, improving the accuracy of atomic refinement, and removing ambiguity in hydrogen bond identification. Outside of secondary structures where hydrogen bonding was predictable a priori, the networks of hydrogen bonds coming from direct observation of hydrogens and acceptor atoms are quite different from those inferred even at 2.8 Å resolution. The implications for understanding viral assembly mean that cryo-EM will likely become the favored approach for high resolution structural virology.